Coordinated-Control Strategy of Photovoltaic Converters and Static Synchronous Compensators for Power System Fault Ride-Through. Issue 15 (13th September 2016) - Yang, Lihui; Liu, Weizeng; Peng, Guoping; Chen, Yun-Guang; Xu, Zhao
Abstract: This article presents a coordinated-control strategy between the photovoltaic converters and the static synchronous compensator to improve the low-voltage ride-through capability of the photovoltaic system according to the grid connection requirement. Within the new strategy, the photovoltaic array can generate relevant active power according to the depth of the grid voltage dip to keep power balance between the two sides of the photovoltaic inverter. A feed-forward compensation reflecting the instantaneous current injecting into the direct current-link from the photovoltaic array is introduced in the controller of the photovoltaic grid-side inverter to smooth the direct current-link voltage fluctuations during the grid fault. It is worthy of special mention that a staged reactive power controller is proposed to distribute reactive power support between the photovoltaic grid-side inverter and static synchronous compensator automatically. The effectiveness of the proposed control strategy has been demonstrated through various simulation scenarios. Compared with conventional methods, the proposed control strategy can not only enhance the low-voltage ride-through capability of the photovoltaic system, but also provide grid support through the active and reactive power control.